2015
DOI: 10.1016/j.jnoncrysol.2015.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Alkali environments in tellurite glasses

Abstract: Neutron diffraction measurements are reported for five binary alkali tellurite glasses, xM2O·(100-x)TeO2 (containing 10 and 20 mol% K2O, 10 and 19 mol% Na2O, and 20 mol% 7 Li2O), together with 23 Na MAS NMR measurements for the sodium containing glasses.Differences between neutron correlation functions are used to extract information about the local environments of lithium and sodium. The Na-O bond length is 2.37(1) Å and the average Na-O coordination number, nNaO, decreases from 5.2(2) for x=10 mol% Na2O to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…Previous research (Dimitriev et al, 1983;Barney et al, 2015) shows the binary tellurium vanadate glasses do indeed contain vanadium ions in two states: V 4+ and V 5+ . As such, these glasses meet the general condition that TMIs be present in more than one valence state, and exploring this ratio is key to determining why these glasses display the conductivity they do.…”
Section: Introductionmentioning
confidence: 95%
“…Previous research (Dimitriev et al, 1983;Barney et al, 2015) shows the binary tellurium vanadate glasses do indeed contain vanadium ions in two states: V 4+ and V 5+ . As such, these glasses meet the general condition that TMIs be present in more than one valence state, and exploring this ratio is key to determining why these glasses display the conductivity they do.…”
Section: Introductionmentioning
confidence: 95%
“…The latter type of bonds interconnects the neighboring chains via very asymmetric Te-O terminal -Te. The bending vibrations of those bonds account for the band near 660 cm -1 [1][2][3][4][5][6]. ) showed a gradual increase.…”
Section: Xrd Analysismentioning
confidence: 99%
“…The structure of binary and ternary telluride glasses [1][2][3][4][5] has been investigated extensively by a variety of experimental techniques [5,6]. It has been reported that the structure of TeO 2 glasses with a small amount of Na 2 O (up to 20 moles %) is a continuous random network of TeO 4 trigonal bipyramids (tbps) and TeO 3+1 polyhedra having one nonbridging oxygen, NBO.…”
Section: -Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Bürger et al [12] studied the glass forming region, phase equilibria and structural investigation of the system and revised the phase diagram. Apart from these studies, Kashchieva et al [15] carried out transmission electron microscope investigations in the system, Halimah et al [16] studied physical properties, Sabry et al [13] studied optical and electrical properties of boro-tellurite glasses and Barney et al [17] realized structural investigation of the TeO 2 eB 2 O 3 system.…”
Section: Introductionmentioning
confidence: 99%